Impassioned Jurisprudence : Law, Literature, and Emotion, 1760-1848. - Stern, Simon, 1971- (Aperçus: Histories Texts Cultures., 2015)
This collection of essays by scholars of the law and literature movement explores the place of the passions in English law of the eighteenth and nineteenth centuries. While some of the essays elucidate the forces of emotion in legal texts, others consider the representation of impassioned jurisprudence in literary texts. Together these essays provide insight into the foundations of modern juridical thought.